Adoption of Advanced Information System for Strengthening Leg Muscles After Knee Replacement Surgery - Lee, Seong-Ran (International Journal of Engineering and Technology, 2019)
This paper is to identify the effect of advanced information system for strengthening leg muscles after knee replacement surgery after artificial joint surgery. The survey conducted a survey of 126 patients who visited an orthopedic surgery from January 8 to March 23, 2018 in the region of M. The general characteristics of the study participants were carried out with X²-test. The research has been obtained the procedure that changed after the surgery by t-test. The practice for strengthening leg muscles after surgery was analyzed by t-test. As a result, first, in terms of men, 52.4% of the experimental group showed a significantly higher than 46.0% of control group(X2=5.26, p<.05). Second, the mean score(57.85±1.72) of the patient's leg edema after the artificial joint surgery was significantly reduced than the mean score(74.19±2.85) before the application of the information system(t=2.17, p<.05). Third, the strength of the legs of patients had increased steadily after 8 days applying information system in the experimental group than control group. Therefore, the information system will be a useful tool for patients to strengthen leg muscles after surgery. lt will also provide infrastructure deployment in the medical information field.